Pesan Dakwah dalam Lirik Lagu Sabyan Gambus Sapu Jagat - Salma Salma Nur Padillah; Irfan Safrudin (UNISBA Press, 2022)
Abstract. Da'wah can be disseminated through various media without reducing the meaning and purpose of da'wah. Of course, there are many things that can be used as a medium of da'wah, one of which is through the media of songs where this art has its own charm and value, of course, and does not bore the audience (the listeners). Religious songs are a type of song that contains a lot of da'wah messages, for example, the song